2011
DOI: 10.1167/iovs.10-5467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graded Cyclic Stretching on Extracellular Matrix–Related Gene Expression Profiles in Cultured Primary Human Lamina Cribrosa Cells

Abstract: Low-level, pulsatile, cyclic strain resets a lower baseline expression of several glaucoma-associated ECM genes. The LC ECM gene response occurs above a fourfold increase in baseline strain (12.5% strain) in vitro. The study supports the use of a nonstatic baseline when studying the effect of stretch (or strain) on the activation of ONH-derived, ECM-producing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Other hypothesis includes oxidative or nitrative stress, both at the level of trabecular meshwork (Sacca et al, 2007) and 21 retinal ganglion cells (Aslan et al, 2008;Tezel, 2006); autoimmune reactions in which an individual's immune system facilitate somatic/axonal degeneration of retinal ganglion cells (Wax and Tezel, 2009); glutamate toxicity (Vorwerk et al, 1999); loss of neurotrophic factors (Pease et al, 2000), etc. However, a various combination of these factors may be involved.The glial cells in the optic nerve head region (lamina cribrosa cells) (Quill et al, 2011), and in particular the astrocytes, the principal glial cells, have been proposed to play an important role in the glaucomatous change in the extracellular matrix in around the ganglion cells (Hernandez, 2000;Hernandez et al, 2008). In primates, alterations in the expression of metalloproteinases (MMPs) and their inhibitors (TIMPs) occur in the optic nerve head of experimental glaucoma (Agapova et al, 2003a).…”
Section: Pathogenesis Of Glaucomamentioning
confidence: 99%
See 1 more Smart Citation
“…Other hypothesis includes oxidative or nitrative stress, both at the level of trabecular meshwork (Sacca et al, 2007) and 21 retinal ganglion cells (Aslan et al, 2008;Tezel, 2006); autoimmune reactions in which an individual's immune system facilitate somatic/axonal degeneration of retinal ganglion cells (Wax and Tezel, 2009); glutamate toxicity (Vorwerk et al, 1999); loss of neurotrophic factors (Pease et al, 2000), etc. However, a various combination of these factors may be involved.The glial cells in the optic nerve head region (lamina cribrosa cells) (Quill et al, 2011), and in particular the astrocytes, the principal glial cells, have been proposed to play an important role in the glaucomatous change in the extracellular matrix in around the ganglion cells (Hernandez, 2000;Hernandez et al, 2008). In primates, alterations in the expression of metalloproteinases (MMPs) and their inhibitors (TIMPs) occur in the optic nerve head of experimental glaucoma (Agapova et al, 2003a).…”
Section: Pathogenesis Of Glaucomamentioning
confidence: 99%
“…Thus, future research should be directed towards exploring the exact causes of optic nerve damage or ganglion cell death. Recent studies have suggested some role of the glial cells, such as, lamina cribrosa cells (Quill et al, 2011) and astrocytes (Hernandez, 2000;Hernandez et al, 2008), in the remodeling of the extracellular matrix in the optic nerve head. How these cells and remodeling of the region plays role in causing ganglion cell death is unclear.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…In these models we mimic the in vivo biomechanical environment in the LCr by growing human ONH astrocytes on flexible, silastic membranes and subjecting the cells to deformation. A similar approach has been used previously on LCr cells (48,49). Other studies have analyzed the protein regulation of cells from the ONH using hydrostatic pressure (45, 50 -53).…”
mentioning
confidence: 99%
“…In addition to the models based on the increase in pressure, models inducing mechanical stretch have been also developed to study alterations occurring in glaucoma. These models use commercially available straining systems allowing a sustained increase in strain or variable pulses [85,86] , whereas control cells are kept in static conditions. Exposure of primary cultures of human lamina cribrosa cells to a mechanical strain of 15% stretch at 1 Hz for 24 h changes the expression of genes related to cell proliferation, growth factor activity, and signal transduction [85] .…”
Section: Stretch-based Modelsmentioning
confidence: 99%
“…Furthermore, stretch changes the expression of genes that regulate the extracellular matrix in these cells, which is prevented by the blockade of calcium channels, highlighting the role of calcium influx in matrix remodeling in glaucoma [87] . In addition, exposure of human lamina cribrosa cells to an elongation of 3% at 1 Hz and then to 12.5 or 20% stretch alters the expression of several genes involved in extracellular matrix dynamics [86] . These studies indicate that stretch-based approaches may also be relevant to the study of alterations in glaucoma, i.e.…”
Section: Stretch-based Modelsmentioning
confidence: 99%